A stony track towards innovation in remote highland regions: Agricultural intensification in the apricot sector of Northern Pakistan - Köster, Mareike; Alam, Iftikhar; Rana, Jai; Wiehle, Martin; Buerkert, Andreas (BioMed Central, 2024)
Abstract Background Traditional farming practices of remote highland regions are usually well adapted to the local agro-ecological and social conditions. There, introduced agricultural innovation geared towards sustainable intensification as a response to changing environments often faces multiple barriers. These may comprise limited market incentives for enhanced production, narrow pathways of knowledge transmission, and infrastructural hurdles. To quantify effects of innovation and sustainable intensification in enhancing smallholders’ livelihoods in the Karakoram Mountains of Northern Pakistan, the present study was conducted with 86 small-holder farmers. We chose interviewees who are involved in the cultivation, processing and/or trading of apricot ( Prunus armeniaca L.), a traditionally important currently eroding fruit crop of the Central Asian highlands. By investigating the status quo of apricot production and producers’ innovative farming practices, we generated an intensification index based on simple agronomic indicators. Explanatory farm and framers’ characteristics, production characteristics, knowledge, and apricot management were tested for their predictive power. Results Although the data show low average profits of 3.8 US$ tree −1 , we found that intensified apricot production can contribute to the provision of nutritious food and increased household income. Age and training of farmers were key factors fostering innovation, while lacking awareness of innovative practices was attributed to slow communication. Rejection of intensification was either due to low-value attribution towards apricot farming or risk aversion. Commonly adopted innovations, particularly sulfur drying, were either well integrated with traditional practices or characterized by low up-front costs and high returns on investment. Conclusions Management intensification may increase farmers’ incomes and retard abandonment of apricot farming and the consecutive loss of associated benefits, such as diversified farm output and improved ecosystem services. Graphical Abstract